Contribution of passive moments to inter-segmental moments during gait: A systematic review. (9th June 2021) - Axel, Koussou; Eric, Desailly; Raphaël, Dumas
Abstract: Inter-segmental moments computed by inverse dynamic during gait come from active moments, due to muscle contraction, but also from passive moments, resulting from the resistance of the periarticular structures to their deformation. The evaluation of the proportion of the inter-segmental moments that can be attributed to passive moments has led to divergent results. Thus, the purpose of this study was to systematically search and synthesize the evidence of the contribution of passive moments to inter-segmental moments during healthy and pathological gait. A broad systematic search was performed including four databases. Thirteen studies met all inclusion criteria. Results showed that passive moments participate to inter-segmental moments during gait in a non-negligible way. For the ankle, the evaluation of the proportion of inter-segmental moment attributed to passive structures is 5-20% around the push-off. For the knee, this proportion is 40–98% during late swing and 10–80% during the single support phase. For the hip, it is 20–50% at push-off. For pathological population, it has been shown that this contribution may sometimes be more important, either due to a smaller inter-segmental moment or a larger passive moment. These results suggest that passive mechanisms can contribute substantially to normal human gait, facilitating the propulsion or the braking of the joint. Passive structures, acting as elastic springs, thus help to reduce the energy cost of gait. For pathological gait, studying the contribution of passive moments to inter-segmental moments can help to better understand the aetiology of the pathology.